Robot operating system for absolute beginners : robotics programming made easy - Joseph, Lentin ([Berkeley, California] : Apress, 2018)
Learn how to get started with robotics programming using Robot Operation System (ROS). Targeted for absolute beginners in ROS, Linux, and Python, this short guide shows you how to build your own robotics projects. ROS is an open-source and flexible framework for writing robotics software. With a hands-on approach and sample projects, Robot Operating System for Absolute Beginners will enable you to begin your first robot project. You will learn the basic concepts of working with ROS and begin coding with ROS APIs in both C++ and Python
Getting started with Ubuntu Linux for robotics -- Fundamentals of C++ for robotics programming -- Fundamentals of Python for robotics programming -- Kick-starting robot programming using ROS -- Programming with ROS -- Robotics project using ROS
Includes index
Keywords: Robots -- Programming; Operating systems (Computers)